Upaya Peningkatan Kesehatan Masyarakat melalui POSBINDU PTM di PMA Jamblangan Seyegan Sleman - Widianti, Emma (Journal of Humanity Dedication, 2024)
The significant increase in cases of Non-Communicable Diseases (NCDs) will place a burden on society and the government, as their treatment requires time, high costs, and advanced technology. NCDs are not contagious but are deadly and lead to unproductive individuals; however, NCDs can be prevented by controlling risk factors through early detection. The upward trend in NCDs has been accompanied by a shift in disease patterns: these diseases were typically experienced by the elderly, but now they are starting to threaten the productive age group. If the trend of young people with NCDs continues to rise, Indonesia's efforts to produce a healthy and intelligent generation toward a developed Indonesia by 2045 will be difficult to achieve. To tackle the high incidence of NCDs, the government introduced the Posbindu PTM program in 2012, which focuses on controlling NCD risk factors within the community. This requires shared understanding and efforts in role distribution and management support for the NCD control program. In 2016, approximately 71 percent of global deaths were caused by NCDs, which kill 36 million people annually. The objective of this PPM activity is to conduct early detection and follow-up on NCD risk factors. The activities include blood pressure checks, body mass index measurement, interviews on risk behaviors, and education on healthy lifestyle behaviors through Posbindu activities at PMA Jamblangan Margomulyo Seyegan.